2020
DOI: 10.3390/ma13071489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grain Size on the Microstructure and Strain Hardening Behavior of Solution Heat-Treated Low-C High-Mn Steel

Abstract: The low-carbon high-Mn austenitic steel microalloyed with titanium was investigated in this work. The steel was solution heat-treated at different temperatures in a range from 900 to 1200 °C. The aim was to receive a different grain size before the static tensile test performed at room temperature. The samples of different grain sizes showed the different strain hardening behavior and resulting mechanical properties. The size of grain diameter below 19 μm was stable up to 1000 °C. Above this temperature, the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…It has been reported that the grain size in the microstructure has a huge impact on the mechanical properties. Fine grains in the microstructure result in higher hardness values and tensile strengths as compared to coarse grains [ 25 ]. In addition, thermal variation in the sample also controls the grain size to a large extent.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the grain size in the microstructure has a huge impact on the mechanical properties. Fine grains in the microstructure result in higher hardness values and tensile strengths as compared to coarse grains [ 25 ]. In addition, thermal variation in the sample also controls the grain size to a large extent.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed in Section 1, rapid metallographic approaches based on edge detection and image binarization have been used to study a wide variety of problems [2][3][4][5][6][7][8][12][13][14][15]. The creation of image-processing algorithms with various levels of sophistication and computational efficiency has been extensively addressed with the introduction of several novel FD methods [38][39][40][41][42][43].…”
Section: Integrated Image Processing Toolsetmentioning
confidence: 99%
“…Tracking changes in the microstructure, including the grain boundary (GB) deformation, dislocation, and structural evolution, is essential because these problems contribute to the overall behavior of the metal [9][10][11][12][13]. In addition, it has been found experimentally that a significant reduction in the grain size is associated with a lower material durability and damage resistance [14,15]. Therefore, an accurate and automatic method for tracking the collective microstructural changes that occur as a result of various external force impacts can substantially facilitate microstructural analysis and modeling, thus shortening the time to the development of new materials and leading to the better operation and maintenance of such materials during their service life [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, high manganese austenitic steels, such as high manganese twinninginduced plasticity (TWIP), transformation-induced plasticity (TRIP) and low-density steels, have attracted much interest due to their potential applications in the automotive industry [1][2][3][4][5]. A large number of studies focus on deformation mechanisms, strain hardening, yield strength, texture, fracture and fatigue, etc.…”
Section: Introductionmentioning
confidence: 99%